Clinical characteristics of patients diagnosed with bilateral sudden sensorineural hearing loss - He, Jun; Jin, Li; Yao, Jacqueline; Mahmoudi, Ahmad; Pan, Zhen; Fu, Jinfeng; Yuan, Qiulin; Liu, Wei (Frontiers in Neurology, 2024)
This study investigated the etiology, clinical features, and prognosis of patients diagnosed with bilateral sudden sensorineural hearing loss (BSSNHL). The clinical data of 100 patients with bilateral sudden hearing loss as a chief complaint treated at Xiangya Second Hospital of Central South University between January 2010 and August 2022, including clinical characteristics, audiometric data, and prognosis, were retrospectively analyzed. These 100 cases accounted for 8.09% (100/1235) of all patients admitted for sudden sensorineural hearing loss (SSNHL) during the same period. Of these, 71 were simultaneous cases and 29 were sequential cases of BSSNHL. Among the 200 ears analyzed in this study, 13, 36, 57, and 94 had mild, moderate, severe, and profound senso-rineural hearing loss, respectively. The overall effective rate after comprehensive treatment was 32%, with significant differences in efficacy and prognosis among different degrees of hearing loss (p<0.05). Comorbidities of hypertension (24 cases), diabetes (14 cases), and coronary heart disease (9 cases) significantly impacted therapeutic efficacy and prognosis in patients with BSSNHL (p<0.05). Compared to unilateral SSNHL, BSSNHL exhibits distinctive characteristics.